Biotechnology, communication and the public: Keys to delve into the social perception of science - Dominique Brossard (Mètode Science Studies Journal: Annual Review, 2019)
The latest biotechnology applications allow for faster and cheaper gene editing than ever before. Many people are calling for a public debate on these issues, including the social, cultural and ethical implications of these applications. On the other hand, the information available to citizens is sometimes contradictory and communication that takes all these aspects into account is important and increasingly necessary. Therefore, understanding public attitudes towards biotechnology should be a priority for the work ahead.